The Wages of Influence: Labor and Management in Postwar Japan - Lewis, Michael (Labour / Le Travail, 2000)
The article reviews the book, "The Wages of Influence: Labor and Management in Postwar Japan," by Andrew Gordon.

The Remaking of the Japanese Working Class - Lewis, Michael (Labour / Le Travail, 1999)
The article reviews and comments on Kazuo Nimura's "The Ashio Riot of 1907: A Social History of Mining in Japan" (1997) and Yuko Ogasawara's "Office Ladies and Salaried Men: Power, Gender, and Work in Japanese Companies" (1998).